L’évolution spatio-temporelle de mortalité par cancers broncho-pulmonaires en France de 1973 à 2016 un marqueur des trajectoires de développement des territoires ? - Zoé Vaillant; Stéphane Rican; Walid Ghosn; Grégoire Rey (Espace populations sociétés)
This article presents an analysis of the spatial distribution of bronchopulmonary cancer mortality in France at the scale of urban units (more than 20,000 or 10,000 inhabitants) between 1973 and 2016 (Cépidc Inserm mortality data). The analysis by city size in eight sub-periods makes it possible to observe different phases of spatial spread of the pathology. Since the main risk factor for this cancer is –by far- smoking, the spatial variations observed refer primarily to the spread and disparities in smoking practices. While the spatial distribution of mortality from bronchopulmonary cancers was mainly associated with the level of industrialization and urbanization in the 1950s to 1980s, social difficulties, access to employment, and the opposition between the most economically dynamic areas and the most marginalized seem to be the most structuring elements today. Thus, areas marked by deindustrialization, difficulties in economic reconversion, small and medium-sized towns far from major urban centres or a large number of cities around the Mediterranean now show a smaller decrease in male mortality and a more rapid increase in female mortality (except in northern cities). Mortality from bronchopulmonary cancers is an additional marker of social difficulties, of the marginalization and progressive detachment of certain areas from the most dynamic areas and the best connected to the leading cities of the national or European urban network.